1979
DOI: 10.1148/133.3.723
|View full text |Cite
|
Sign up to set email alerts
|

Radionuclide Bone Imaging as a Means of Differentiating Loosening and Infection in Patients with a Painful Total Hip Prosthesis

Abstract: Twenty patients with 23 painful total hip prostheses were examined by radionuclide imaging (20 cases), arthrography (11 cases), needle aspiration (9 cases), and surgery (19 cases) for the purpose of assessing loosening and/or infection. Bone imaging was most accurate, showing three main distributions of activity: (a) ectopic calcification, (b) focal increased activity at the upper and lower ends of the femoral prosthesis, and (c) diffuse activity. These findings suggest that infection and loosening can be diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1
4

Year Published

1985
1985
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(16 citation statements)
references
References 0 publications
2
9
1
4
Order By: Relevance
“…In one patient in our study, the correct diagnosis of infection could only be made with serial radiographs; PET and bone scintigraphy yielded false-negative findings. At bone scintigraphy, focally increased radionuclide uptake around the prosthesis is commonly considered to represent loosening, while diffusely increased uptake is commonly considered to represent infection (36,37). However, infection may also be present in prostheses with focal uptake patterns (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…In one patient in our study, the correct diagnosis of infection could only be made with serial radiographs; PET and bone scintigraphy yielded false-negative findings. At bone scintigraphy, focally increased radionuclide uptake around the prosthesis is commonly considered to represent loosening, while diffusely increased uptake is commonly considered to represent infection (36,37). However, infection may also be present in prostheses with focal uptake patterns (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic algorithm of loosened hip prostheses begins with simple serologic blood tests and radiographic studies . These tests have high sensitivity, but they lack the adequate specificity to confirm infection.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic algorithm of loosened hip prostheses begins with simple serologic blood tests and radiographic studies. 29 These tests have high sensitivity, but they lack the adequate specificity to confirm infection. The culture of aspirated joint fluid has high specificity but the aspiration of the hip joint is invasive, technically demanding and require fluoroscopic guidance.…”
Section: Discussionmentioning
confidence: 99%
“…Williamson and coworkers [16] found that focal periprosthetic uptake was associated with aseptic loosening, whereas diffuse uptake around the femoral and acetabular components was associated with infection.…”
Section: Bone Scintigraphymentioning
confidence: 99%